Redução de inóculo de Aphelenchoides besseyi em sementes de Brachiaria brizantha tratadas com óleos essenciais - Monteiro, Thalita Suelen Avelar (2014)
Essencial oils were tested to control Aphelenchoides besseyi in Brachiaria brizantha cv. 'Marandu' seeds. Seeds naturally infested with A. besseyi were treated with essential oils of mustard (Brassica nigra), cinnamon (Cinnamomum zeylanicum), verbena (Lippia citriodora) and Bioprotector (r)(a commercial product based on formulation of plant extracts and essentialoils), in concentrations of 0.5% and 1.0%. The effects of the same treatmentsafter direct application on juveniles nematodes were evaluated invitro. All treatments were less effective to control the nematode in theseeds (in vivo) comparing to the in vitro test.The treatments did not eradicate the nematode from the seeds. However, theessential oils of cinnamon and verbena (in both concentrations), mustard (1.0%),as well as Bioprotector (r)(1.0%), reduced the seed population of A. besseyi. Mustard oil (1.0%) stoodout for its nematicide action with no effect on seed germination.